Public procurement directives in the European Union: a study of local authority purchasing - Martin, Stephen; Cox, Andrew; Hartley, Keith (1999)
Prompted by the Single European Market initiative, virtually all public procurement, except for defence equipment, is now subject to European Union rules which prohibit discriminatory (buy national) purchasing policies. This paper examines the impact of recent procurement Directives on local authority tendering and contract award behaviour (compliance), and considers whether the legislation has been successful in opening-up such public procurement to international competition. Although local authorities are making extensive use of the Official Journal to advertise their requirements, there is evidence that purchasers do not always adhere to the new legislation and it is not obvious that adherence to the legislation is improving. Moreover, an analysis of local authority contract award data for 1993 revealed that almost all contracts were won by domestic firms. However, doubts about the ultimate ownership of such firms and the sourcing of components means that there remains considerable scope for further work. - Reproduced
Keywords: European union